STRATEGI PENGEMBANGAN DAN PEMASARAN DESA WISATA SUKARARA YANG TERINTEGRASI DI KECAMATAN JONGGAT KABUPATEN LOMBOK TENGAH - Lalu Adi Permadi; Harmi Widiana; Rusminah HS; Muttaqillah Muttaqillah (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research is aimed to design the accurate strategy to be implemented in integrated Sukarara Tourism village development and marketing according to the village environment condition and to identify which strategy that has to be prioritized by the government and local participants. Data that used in the research are primary and secondary data. Primary data were mainly obtained by interviewing the local stakeholder, while secondary data were taken from library study and government data. Result of this research suggested the main strategy that can be implemented in developing and marketing Sukarara tourism village are develop the alternative tourism attraction while still maintain the songket weaving as main appeal of the village by preparing the new design which more interesting to the visitor, prepare the internet promotion, organise the local people as culture tourism guide and arrange the village spatial design.